Suppression of low-energy dissociative electron attachment in Fe(CO)5 upon clustering - Lengyel, Jozef; Papp, Peter; Matejčík, Štefan; Kočišek, Jaroslav; Fárník, Michal; Fedor, Juraj (Beilstein Journal of Nanotechnology, 2017)
In this work, we probe anion production upon electron interaction with Fe(CO)5 clusters using two complementary cluster-beam setups. We have identified two mechanisms that lead to synthesis of complex anions with mixed Fe/CO composition. These two mechanisms are operative in distinct electron energy ranges. It is shown that the elementary decomposition mechanism that has received perhaps the most attention in recent years (i.e., dissociative electron attachment at energies close to 0 eV) becomes suppressed upon increasing aggregation of iron pentacarbonyl. We attribute this suppression to the electrostatic shielding of a long-range interaction that strongly enhances the dissociative electron attachment in isolated Fe(CO)5.
Keywords: aggregation effects; dissociative electron attachment; FEBID; iron pentacarbonyl; long-range interactions